If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7p + -3(2 + -5p) = 5(p + -6) + -12 -7p + (2 * -3 + -5p * -3) = 5(p + -6) + -12 -7p + (-6 + 15p) = 5(p + -6) + -12 Reorder the terms: -6 + -7p + 15p = 5(p + -6) + -12 Combine like terms: -7p + 15p = 8p -6 + 8p = 5(p + -6) + -12 Reorder the terms: -6 + 8p = 5(-6 + p) + -12 -6 + 8p = (-6 * 5 + p * 5) + -12 -6 + 8p = (-30 + 5p) + -12 Reorder the terms: -6 + 8p = -30 + -12 + 5p Combine like terms: -30 + -12 = -42 -6 + 8p = -42 + 5p Solving -6 + 8p = -42 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -6 + 8p + -5p = -42 + 5p + -5p Combine like terms: 8p + -5p = 3p -6 + 3p = -42 + 5p + -5p Combine like terms: 5p + -5p = 0 -6 + 3p = -42 + 0 -6 + 3p = -42 Add '6' to each side of the equation. -6 + 6 + 3p = -42 + 6 Combine like terms: -6 + 6 = 0 0 + 3p = -42 + 6 3p = -42 + 6 Combine like terms: -42 + 6 = -36 3p = -36 Divide each side by '3'. p = -12 Simplifying p = -12
| -4(x-8)=18+3 | | 9x+70=9x+92 | | -4+3=35 | | Fx=5x^2-3x+4 | | 5x-10x+14x=-3x+6 | | 2x-9=22 | | 3r-8-9r= | | 6x+7=-21 | | 7+5x=5x-12 | | (4+i)z=-3+2i | | 3(2x+5)-x=2x+5 | | 71-u=259 | | 38+1x=20 | | q-5q= | | 2x^2+bx+36=0 | | 38+1x=80 | | 38+1x=38 | | 3+6x=13+6c | | 2.5w-5=2w+5 | | ln(7x-1)=5 | | A^3-80a+1024=0 | | -6-4(2f+8)= | | 3(2x+5)-x=6x+20 | | 4z^2+9=12z | | 4x+1=2y+25 | | 9.9-0.3= | | -4a+5a=6-27 | | 5k-9k= | | X^2+y^2-16x=0 | | 3(2x+5)-x=5x+13 | | 2x-8y+6x+5y= | | 5n+3=4-(6-5n) |